ENSURING ELECTRICAL SAFETY IN NETWORKS WITH RESISTIVE NEUTRAL GROUNDING - Raximov, F.M. (SCIENCE and SOCIETY, 2024)
This article focuses on the important role of neutral resistor grounding in ensuring the safety of personnel and equipment in the energy sector. The considers the problem of compliance with uniform safety standards with the choice of grounding parameters of resistors, connecting them to protection devices and monitoring their condition.